Style shifting on X: a comparison of Saudi male and female academics - Aldhuwaihi, Hajar; Albawardi, Areej (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study explores the phenomena of diglossia and style shifting among Saudi academics on X, with a particular focus on gender differences in these linguistic practices. The research aims to contribute to the understanding of the complex interplay between language, gender, and digital communication in the Arabic context. The study employs a mixed-methods approach, combining qualitative and quantitative analyses of a corpus of tweets from 80 Saudi academics (40 male and 40 female) across four Saudi universities. The data, consisting of 800 tweets, were systematically analysed to identify instances of style shifting across lexical and functional categories. The findings reveal an occasional presence of style-shifting in the digital communication of Saudi academics, with both male and female participants employing non-standard forms of Arabic in their posts. The results show that female academics have a slightly higher overall rate of style shifting, with males using more lexical shifts and females more functional shifts. The pervasive nature of style shifting across lexical and functional categories in the posts of Saudi academics underscores the need for a more dynamic approach to the study of language use and variation in the Arabic context. The findings have significant implications for Arabic linguistics, language variation theories, and language education, particularly in the context of teaching Arabic as a foreign language. The study serves as a catalyst for further research on the intersection of language, gender, and digital communication in the Arab world, contributing to ongoing efforts to promote linguistic diversity, cultural understanding, and social justice in the digital age.